2016
DOI: 10.1213/xaa.0000000000000202
|View full text |Cite
|
Sign up to set email alerts
|

Plagiarism in Personal Statements of Anesthesiology Residency Applicants

Abstract: Plagiarism by residency applicants in their personal statements, as well as sites that sell personal statements, have been described, and led in 2011 to advice to avoid plagiarism and the caution that plagiarism detection software was available. We screened personal statements of 467 anesthesiology residency applicants from 2013-2014 using Viper Plagiarism Scanner software, and studied them for plagiarism. After quotes and commonly used phrases were removed, 82 statements contained unoriginal content of 8 or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…[3][4][5][6] Other studies have identified significant rates of plagiarism in personal statements. [7][8][9] Such behaviours are seen as a harbinger of future problems and are dealt with harshly.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6] Other studies have identified significant rates of plagiarism in personal statements. [7][8][9] Such behaviours are seen as a harbinger of future problems and are dealt with harshly.…”
Section: Resultsmentioning
confidence: 99%
“…The 2% rate of plagiarism ("plagiarized high") in both US and non-US AMCAS applicants is less than the reported rates in personal statements of applicants to certain residency programs. 1,2 Parks and colleagues discovered that 13.6% of personal statements from non-US medical school graduates and 4.0% from US medical school graduates contained plagiarized material in applications to their anesthesiology residency program. 2 As a result of their study, they now screen the personal statements of every applicant and reject those found to have plagiarism.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Parks and colleagues discovered that 13.6% of personal statements from non-US medical school graduates and 4.0% from US medical school graduates contained plagiarized material in applications to their anesthesiology residency program. 2 As a result of their study, they now screen the personal statements of every applicant and reject those found to have plagiarism. Segal et al discovered plagiarism in 5.2% (95% CI, 4.6% to 5.9%) of statements submitted to their five Published online August 6, 2019 largest residency programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations